The Rhetorical Strategy of Putri Karlina in Building the Image of a Female Leader in the Garut Regional Election - Muzaqi Hersandi, Revy; Nurhadi, Zikri Fachrul; Partiwi, Resty Mustika (Sinergi International Journal of Communication Sciences, 2025)
Women’s representation in Indonesian local politics is hindered by structural and cultural barriers, including gender stereotypes that deem women less suitable for leadership. This study explores how Putri Karlina navigated these challenges during the 2024 Garut Regional Election. Using a qualitative approach, data were gathered through in-depth interviews with her media team, observations of campaign activities, and analysis of social media content. The study focuses on Karlina’s rhetorical strategies, drawing on Aristotle’s ethos, pathos, and logos. The results show that Karlina strengthened her credibility (ethos) by consistently engaging with the community and addressing social issues. She used emotional appeals (pathos) through personal stories, local language, and empathetic interactions to connect with voters. Additionally, she employed logical arguments (logos) by presenting data-driven visions and concrete solutions to public problems. This combination of rhetorical strategies not only enhanced her public image as a competent and empathetic leader but also helped overcome gender biases in a male-dominated political environment. The findings contribute to the understanding of gender dynamics in political communication, especially in the context of local elections.